Decision support system fuzzy goal programming model to optimize benefits of SME furniture - Purnama, Jaka; Setiawan, Budi; Santoso, Imam; Yanuwiadi, Bagyo (International Journal of Engineering and Technology, 2019)
SME Furniture currently has not done an optimal analysis of production amount. The amount of production is based solely on the needs of the consumer, resulting in improper production costs. This study aims to determine the optimal amount of production of each product using Fuzzy Goal Programming (FGP) model. In obtaining optimal benefits consider the cost of labor costs and raw material costs. Fuzzy goal programming model is used for decision making in determining the amount of production on each product type. The analysis has done by maximizing profits and minimize labor, raw materials and working time. The results of this study indicate that the fuzzy goal programming model can optimize the clothing in furniture SMEs by 30%.Â
Keywords: Fuzzy Goal Programming; Furniture; SME; Optimal; Production.